Land cover changes in tidal salt marshes of the Bahía Blanca estuary (Argentina) during the past 40 years - Pratolongo, Paula Daniela (2013)
The present work describes land cover changes in the inner section of Canal Principal, in the Bahía Blanca estuary. The study area is subjected to a rising relative sea level, large interanual variations in rainfall, and recent changes human in land use. We used historical aerial photographs, high resolution satellite images, and GIS to quantify changes in land cover for the years 1967, 1996, and 2005. The replacement of Sarcocornia perennis marshes and halophytic shrub-like steppes by mudflats is a recurring pattern through the area. We estimated a total loss to mudflats of 33 and 6% of the area of marshes and steppes, respectively, and it may reflect increased erosion of relict Holocene coastal terraces in response to a rising sea level. Human activities have played a significant role in reshaping coastal landscape, particularly in the harbor area. Fifty percent of the area originally covered by shrub-like steppes and 33% of the Sarcocornia perennis marshes were replaced by human land uses. Major changes correspond to dredged spoil deposition and landfilling. One of the most striking changes observed is the increase of the area covered by Spartina alterniflora marshes. This type of replacement suggests the occurrence of depositional environments that, at least locally, allow bed elevation and vegetation growth. In the harbor area, an enhanced sedimentation may result from maintenance dredging. At the mouth of Maldonado channel, sediment deposition may occur during extraordinary heavy rainfall associated to El Niño.